Effect of biopriming of radish (Raphanus sativus) seed with some antagonistic isolates of Trichoderma (The Journal of Plant Protection Sciences, 2023)
Application of biocontrol agent can be done  in three ways (i) seed treatment, (ii) soil treat ment and (iii) foliar spray. Seed treatment has  been considered the most convenient of the  three as it is required in less amounts with  higher efficacy. Seed being an essential com ponent of agriculture acts as a passive carrier  of many diseases. Seed treatment with bio control agents may serve as an important tool  for managing many soil-borne and seed borne  diseases. This process is known as  ‘biopriming’. Goals for biological seed treat ment include control of soil borne pathogens,  colonization and protection of subterranean  plant parts, and increased plant growth. Effec tive biocontrol agents have been developed  for control of severe seed and seedling patho gens. Several researchers have reported the  biological seed treatments for the protection  of seed and control of pathogens causing  seedling diseases (1,15,3). Similarly several  scientists have got positive results of disease  control and increased plant growth and yield  in vivo and under field condition (6,4,2,11).  The efficacy of biological seed treatment is  influenced by soil pH and iron concentration  (14), moisture, temperature and inoculums  density of the pathogen (9). Trichoderma spp.
Keywords: carboxy methyl; cellulose (CMC); laminar